Infectious Diarrhea Due to Clostridium perfringens - Larson, H. Elliott; Borriello, S. Peter (The Journal of infectious diseases, 1988)
In Clostridium perfringens food poisoning, an association between diarrhea and fecal enterotoxin is well established. Enterotoxin is found only in feces from symptomatic or infected persons and is absent from those of convalescent or healthy subjects. A rise in titer of antibody to the enterotoxin has been documented, and administration of greater than or equal to 10 mg of purified enterotoxin to human volunteers produced diarrhea and abdominal pain. The authors have examined fecal specimens from cases of presumed infections diarrhea for the presence of bacterial exotoxins; earlier, they described the discovery of C. perfringens enterotoxin in 11 patients with presumed infectious diarrhea. This series has now been extended to 50 patients and confirms C. perfringens as a cause of infectious diarrhea unassociated with poisoning from food.